Athapascan fishing camp on the Yukon River, Alaska, ca. 1904 - Nowell, Frank H., 1864-1950
Athapascan fishing camp on the Yukon River, Alaska, ca. 1900-1906. Shows three huts, raised on pilings. Stamped on image: Photo by F. H. Nowell